Research progress of non-drug therapy for post-stroke patients with cognitive impairment (脑卒中后认知障碍患者非药物治疗的研究进展) - SONG Wanchen (宋宛宸); DENG Ying (邓颖); HUANG Shan (黄山); LI Yang (李洋) (中西医结合护理)
Cognitive impairment after stroke is one of the common complications of stroke, which seriously affects the quality of life and prognosis of stroke patients. This paper aims to analyze the risk factors, evaluation and intervention measures of post-stroke cognitive impairment (PSCI) by collecting literature data in the past five years, summarize the clinical studies on non-drug treatment, further propose all-round extension, standard and high-quality non-drug treatment interventions, and provide clinical basis for standardizing non-drug treatment of PSCI patients. (脑卒中后认知障碍(PSCI)是脑卒中患者常见并发症之一, 严重影响患者的生活质量及预后。本研究通过搜集相关文献资料, 分析PSCI的危险因素、评估及干预措施, 总结其非药物治疗在临床的应用研究进展, 为进一步制定全方位、科学化、规范化、优质化的非药物治疗干预措施提供参考。)